Application of fuzzy logic to land suitability for rubber production in peninsular Thailand - Van Ranst E; Groenemans R; Sinthurahat S; Tang H (Geoderma, 1996)
The quantitative impact of land qualities on rubber production (Hevea brasiliensis) using the theory of fuzzy logic was evaluated. This theory was applied to a land suitability assessment for rubber production in the northern part of the rubber growing area of peninsular Thailand. The method proposed differed from the usual technical land evaluation procedures by : (1) the use of an explicit weight for the effect of each land quality on crpo performance ; (2) the way the evaluation of land qualities was combined into a final land suitability class or land suitability index. The methodology was tested by comparing the estimated yields and land indices calculated by the fuzzy set theory with those obtained by the conventional procedures : (1) maximum limitation method ; (2) parametric-Storie method ; (3) multiple linear regression. In the last approach the land index was replaced by the predicted relative yield from multiple regression on the various land qualities. The considered rubber clone, RRIM 600 is grown on a wide range of soils under different climatic conditions and the best relationship was given by the fuzzy set approach which illustrated the potential usefulness of this theory in land evaluation.
Source Year: 1996
Keywords: Fuzzylogic; Hevea brasiliensis; Land evaluation; Thailand